Mechanism of miR-4465 targeting PTEN-mediated autophagy of astrocytes in epilepsy - Zhao, Jinhua; Tang, Jihong; Shi, Xiaoyan (Journal of Medical Biochemistry, 2025)
Objective To investigate the mechanism of miR-4465 targeting PTEN-mediated autophagy of astrocytes in epilepsy. Methods Serum samples were collected from children with epilepsy and healthy children. Exosomes were extracted from the serum samples and their quality determined. miRNA sequencing was performed on the exosomes, and abnormally expressed miRNAs in the serum exosomes of patients were analyzed and miR-4465 expression was verified by quantitative PCR. Targes of miR-4465 have been predicted by bioinformatics, and GO and KEGG analyses were performed on the target genes. HEK293 cells were cultured, and the relationship between miR-4465 as well as its targets has been examined using dual-luciferase reporter method. Astrocytes were cultured, and to verify effects of miR-4465 on PTEN expression, quantitative PCR as well as WB have been applied to detect miR-4465 as well as PTEN expressions after miR-4465 overexpression. Moreover, CCK-8 as well as have been performed for detecting changes in growth as well as autophagy-related proteins ATG5 and Beclin1 expressions after miR-4465 overexpression. Results miR-4465 was markedly increased in serum exosomes. Bioinformatics analysis found the differentially expressed miR-4465 target genes were mainly enriched in molecular binding, molecular function regulation, and other molecular functions, and participated in cell adhesion, cell-extracellular matrix receptor interaction, and the Rap1 signaling pathway. PTEN has been predicted as a miR-4465 target, meanwhile, results of dual-luciferase reporter assay confirmed interaction between miR-4465 as well as PTEN. Quantitative PCR as well as WB results suggested PTEN was lowly expressed in serum exosomes of patients with epilepsy, while increased miR-4465 expression inhibit level of PTEN. CCK-8 as well as WB results suggested miR-4465 could suppress the growth of astrocytes and promote ATG5 as well as Beclin1 expression; finally, up-regulation of PTEN partially alleviate effects of miR-4465 on astrocytes growth as well as autophagy. Conclusion miR-4465 can target and regulate PTEN to promote autophagy in astrocytes.
Keywords: Astrocytes; miR-4465; PTEN; Autophagy